Charged nanoparticles produced by splashing of raindrops. Issue 13 (14th July 2015) - Kamra, A. K.; Gautam, A. S.; Siingh, Devendraa
Abstract The mobility distribution of ions generated by splashing of raindrops is investigated. Our observations show four maxima in the mobility distribution in the small, intermediate, light large, and heavy large ion size ranges. Ion concentration of all categories increases as the rain intensity increases to ~ 50–60 mm h−1 and then tends to level off for higher rain intensities. Negative ion concentration is always more than that of positive ions. However, positive small ions of mobility ≥ 2–3 cm2 V−1 s−1 which are also generated during splashing are more numerous than negative ions. Our observations show that the mechanism responsible for the generation of intermediate ions is more efficient than that for the generation of heavy large ions during periods of high rain intensity. Relative roles of Lenard and Blanchard effects are suggested in generating excess of negative intermediate ions in the initial stages and excess of positive cluster ions, in the later stages of a rain shower, respectively.